Psychometric properties of Colquitt’s Organizational Justice Scale in Argentine workers - Omar, Alicia (2018)
Organizational justice refers to workers’ perceptions of what is fair and unfair in their workplaces. The aim of the present study was to provide evidence of the factorial validity and psychometric properties of the Argentine version of Colquitt’s Organizational Justice Scale. To achieve this objective, an empirical, quantitative, instrumental study with a cross-sectional design was conducted. Data were obtained from a convenience sample of 406 employees (212 men and 194 women) of different Argentine organizations. Confirmatory factor analysis results supported the four-factor structure of the scale (distributive, procedural, interpersonal, and informational justice). The instrument showed good reliability indices (ordinal alpha and composite reliability values greater than .80) and adequate discriminant and convergent validity (average variance extracted indices greater than .60). These psychometric characteristics make the validated scale a useful tool to measure justice perceptions within Argentine organizations.